2022
DOI: 10.3390/ijerph192113899
|View full text |Cite
|
Sign up to set email alerts
|

Does Exercise Training Improve Cardiac-Parasympathetic Nervous System Activity in Sedentary People? A Systematic Review with Meta-Analysis

Abstract: The aim of this study was to investigate the training-induced effect on cardiac parasympathetic nervous system (PNS) activity, assessed by resting heart rate variability (HRV) and post-exercise heart rate recovery (HRR), in sedentary healthy people. Electronic searches were carried out in PubMed, Embase, and Web of Science. Random-effects models of between-group standardised mean difference (SMD) were estimated. Heterogeneity analyses were performed by means of the chi-square test and I2 index. Subgroup analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 126 publications
1
12
0
1
Order By: Relevance
“…The consistency and reproducibility of HRV measurements in both assessments demonstrated that they accurately captured the autonomic response to the exercise protocol, thus supporting the method's reliability in this population. These findings align with previous research that has demonstrated the efficacy of HRV as a tool for evaluating autonomic function in various populations, including older adults [1,[5][6][7][8][9][10][11][12][13]. Using HRV measurements for this purpose could help clinicians identify and monitor individuals at higher risk, leading to earlier interventions and better outcomes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The consistency and reproducibility of HRV measurements in both assessments demonstrated that they accurately captured the autonomic response to the exercise protocol, thus supporting the method's reliability in this population. These findings align with previous research that has demonstrated the efficacy of HRV as a tool for evaluating autonomic function in various populations, including older adults [1,[5][6][7][8][9][10][11][12][13]. Using HRV measurements for this purpose could help clinicians identify and monitor individuals at higher risk, leading to earlier interventions and better outcomes.…”
Section: Discussionsupporting
confidence: 87%
“…The cardiac modulatory effects of ANS can be examined noninvasively through changes in the time intervals between successive R-R intervals in the heart, also known as heart rate variability (HRV) [4]. Moreover, there has been a growing interest in evaluating the HRV response to physical exercise since it reflects a functional autonomic modulation in relation to the active life of people from health to disease [1,[5][6][7][8][9][10][11][12][13]. Evidence shows that effort-related cardiovascular reactivity is associated with executive function and physical fitness [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…From a chronic point of view, physical activity could regulate the activity of the autonomic nervous system (ANS). Indeed, a recent meta-analysis showed a slight increase in RMSSD and HF after a PA program reflecting an increase in parasympathetic modulation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…[33] Indeed, data from meta-analysis concluded that exercise training increases cardiac parasympathetic nervous modulation among sedentary people. [34] In addition to more physical activity and less sedentariness, high quality of sleep was another key lifestyle factor responsible for the reduced cardiovascular risk. Therefore, our data showed that significant associations were found of healthy sleep habits (represented by subjective sleep quality, use of sleep medication, sleep efficiency, and average total sleep time) with lower PWV parameters, and of bad sleep efficiency (sleep efficiency and wake after sleep onset) with ankle-brachial index right, inflammatory biomarkers (IL-6, TNF-α, and CRP), appetite-regulating biomarkers (PY-Y and ghrelin), and leptin.…”
Section: Discussionmentioning
confidence: 99%